Introduction to global logistics delivering the goods - Manners-Bell, John (Kogan Page, 2017)
"The new edition of Introduction to Global Logistics considers how the logistics industry has developed; how it is influenced by macro-economic factors and demand-side trends; what the risks are to the industry and how it will develop over the coming years. Author John Manners-Bell examines individual logistics segments looking at each one's unique microeconomic dynamics. He explains how logistics companies' revenues and profitability are affected by a downturn and how this is governed by such factors as whether they own assets or manage them.Chapters define, explore, and describe six key logistics segments: freight forwarding, contract logistics, shipping, road freight, air cargo, and express, while also examining the individual supply chain dynamics and logistics demands of the major vertical sectors: Automotive, Chemical, Pharmaceutical, Retail, Consumer, and High Tech. The book covers important trends and developments that are shaping the industry, including 3D printing, megacities, and post-harvest food losses"...